Miniature size multiband planar patch antenna fabricated on a bioplastic substrate - Ahsan, M.R.; Islam, M.T.; Ullah, M.H.; Arshad, H.; Ali, M.T. (De Gruyter Open, 2015)
In this article, a simple design of rectangular microstrip feed planar antenna with wide arcs and square shape slot is proposed for Radio Frequency Identification (RFID), Worldwide Interoperability for Microwave Access (WiMAX) and C/X-band wireless communications. The prototype of the antenna has been fabricated 1.0 mm thick ceramic filled bioplastic substrate by using optimal dimension obtained from design/simulations and antenna performances are experimentally tested. The experimental results confirm the impedance bandwidths for S11 <= -10 dB are of 712 MHz (0.355-1.067 GHz), 1.38 GHz (2.92-4.3 GHz) and 2.46 GHz (6.55-9.01 GHz) for 0.788, 3.34 and 8.01 GHz band respectively. The proposed antenna shows almost steady and symmetrical radiation patterns for all three bands with the maximum gains of 1.37, 2.8 and 3.56 dBi respectively. Based on the antenna performances, it can successfully cover the frequency band requirement for RFID, WiMAX and C/X-band applications.